The Social Relationship of Top Management Team and Corporate Green Innovation: Based on the Perspective of “Surname Relationship” - Peng Liu; Tongxu Wang (SAGE Open)
We study the influence of the “surname relationship” of the senior management team on corporate green innovation by taking the A-share listed companies in Shanghai and Shenzhen from 2012 to 2022 as A sample. The results show that the “surname relationship” of senior management team has inhibitory effect on corporate green innovation. The mechanism effect test shows that the “surname relationship” affects the green innovation of enterprises by hindering the formation of multiple cognitive models of teams and weakening the internal supervision mechanism. This paper has enriched the relevant literature on the economic consequences of surname-related culture and the influencing factors of corporate green innovation, and has inspiration and reference significance for improving corporate governance structure and enhancing corporate green innovation ability.